Does Brand Image and Attributes of Selecta Park Influence Revisit Intention through Satisfaction as a Mediating Variable? The Case of Toursm Park’s Visitors - Nur Hidayatul Istiqomah; Ratih Juliati; Djoko Sigit Sayogo (Manajemen Bisnis, 2023)
The purpose of this study is to investigate the relationship between visitors' intention to revisit Selecta Tourism Park in Batu City and the brand image of the destination, the destination's attributes, and their satisfaction as a customer. The study aims to examine whether customer satisfaction mediates the relationship between these factors and visitors' intention to revisit the park. The sampling technique for this study used random sampling of 170 visitors to her Selecta Tourism Park for partial least squares data collection and analysis. The findings of this study reveal several significant relationships. Firstly, there is a direct positive influence of customer satisfaction, destination brand image, and destination attributes on visitors' intention to revisit the park. Secondly, destination attributes and destination brand image have a positive impact on customer satisfaction. Lastly, there is an indirect effect of destination brand image and destination attributes on visitors' intention to revisit the park through customer satisfaction as a mediating variable